Utilization Efficiency of Yolk Egg on Maanvis (Pterophyllum scalare) Embryos and Larvae in Different Incubation Temperatures - T. Budiardi; W. Cahyaningrum; I. Effendi (Jurnal Akuakultur Indonesia)
This study was performed to determine the efficiency of yolk egg utilization in embryos and larvae, hatching rate, incubation time to hatch, and growth rate of maanvis (Pterophyllum scalare) larvae incubated at room remperature, 27oC, and 30oC.  Results of study showed that yolk egg utilization efficiency of embryos and larvae incubated at 30oC was 73.70% and 0,18%, respectively, and no different with that of room and 27oC incubation temperatures.  Hatching rate of eggs incubated at 30oC (84.75%) was also same with that of other treatments.  However, incubation time to hatch (27.41 hours) was shorter than that of other treatments.  The growth rate by length of larvae (2.16%) and survival rate (75.28%) incubated at 30oC was also higher compared with that of other treatments.  Thus, in general, optimum temperature for egg hatching and larval rearing of maanvis was 30oC.